THE STUDY RESULTS OF ADAPTIVE-ECOLOGICAL TRAITS OF THE NEW VARIETIES AND PROMISING LINES OF WINTER SOFT WHEAT IN THE RYAZAN REGION - O. V. Levakova (Зерновое хозяйство России, 2019)
A number of objective reasons for the modern agrarian complex show that it is necessary to orient the most part of the agricultural establishments to a wider introduction of environmentally adaptable varieties. Due to the relevance of this problem, the article analyzes the study results of the competitive variety trials (2016–2018) of 6 varieties, 2 of which are on the SVT, and 11 breeding lines of winter wheat of local selection according to the parameters of ecological adaptability in the agricultural zone of the Ryazan region. There were studied such indicators as stress tolerance, genetic flexibility, coefficient of variation, coefficient of adaptability, yield range, index of stability and indicator of PUSS. As a result of research, it was found that the yield of the standard variety “Angelina” was 7.59 t/ha. The varieties “Glafira”, “Okskaya Krasa” (8.25 and 8.31 t/ha, respectively) produced larger average productivity than the standard variety. The breeding lines “L 45/18”, “L 48/18”, “L 49/18”, “L 65/18”, “L 64/18”, “L 46/18”, “L 63/18” had an average productivity of 7.72 to 8.16 t/ha. It was established that the studied winter wheat varieties and lines had different stress resistance (–0.9...–3.1), a large variation in genetic flexibility (6.9–8.34), different stability index (3.4–19.0) and PUSS (39.6%–223.6%). It was found that only 10 (58.8%) varieties and lines out of 17 studied ones had an average adaptability factor higher than 1. The study has identified that the variety “Glafira” and the breeding lines “L 43/18”, “L 44/18”, “L 45/18” are the most adaptable and stable ones in the conditions of the Ryazan region.